Old school - Kinney, Jeff (Kinney, Jeff. Diary of a wimpy kid, 2017)
THE ONE WITH THE SCARY SCHOOL TRIP The tenth laugh-out-loud, fully-illustrated Diary of a Wimpy Kid book from #1 international bestselling author Jeff Kinney! A global phenomenon with 250 million copies of the series sold worldwide! Greg Heffley's parents are convinced life was better back in the old days. But Greg isn't so sure that a life without electronics, central heating and working plumbing sounds all that fun ... And so, despite his best efforts, he is sent off to Hardscrabble Farm to learn about hard work and the great outdoors. Will Greg be able to survive a week out in the wild? Or will his school trip be a complete DISASTER?